Analisa Tarif Jasa Layanan Sampah Dalam Upaya Peningkatan Pengelolaan Persampahan di Kecamatan Ujungberung - Aqilla Nabil Mukharam; Kancitra Pharmawati (Fakultas Teknik, 2021)
Unfulfillment of waste service ratetarget, low-quality of waste temporary shelter, and the basic needs to increase waste service rates become the foundation to analyze the financial aspect. This can be conductedby calculating and analyzing public’s Willingness to Pay (WTP) to waste management service improvements in Ujungberung Sub-District. The objectives of this research are to know the percentage of people’s WTP towards the rise of waste service rates and analyze factors that can affect the WTP. The chosen method for this research is Contingent Valuation Method (CVM) with Payment Card as its technique. By using Cross-Section method, there are 66 people selected to be the samples of this study. Online questionnaire is used to collect the data. The percentage of public’s WTP is 88% with the value of average WTP is Rp 31.288 and the value of total WTP is RP 113.575.000. Based on the multiple linear regression analysis, the factors significantly affecting the value of WTP are age and existing waste service rates.